Network flow optimization in the formulation of an investment project in Tecamachalco, Puebla - Medel Chavéz, Gonzalo; Arana-Coronado, Oscar Antonio; García-Sanchez, Roberto Calos; Valdivia Alcalá, Ramón (Revista Mexicana de Ciencias Agrícolas, 2022)
Using linear programming, a network flow model was formulated to optimize the use of the land of small producers in the area of the Tecamachalco Valley, Puebla, Mexico. The optimal crop pattern was estimated in order to increase net profits over a production horizon and obtain financial indicators such as NPV, IRR and B/C R. These values were compared with the traditional methodology of project evaluation. The production horizon was five years for five horticultural crops: onion, tomato, bell pepper, cucumber and zucchini. The results indicated that the optimal crop pattern was to produce tomato in spring-summer (s-s) and bell pepper in autumn-winter (a-w). A NPV of 295 229.84 pesos, an IRR of 68.64% and a B/C ratio of 1.52 were obtained. The net profit of the production plan was 7 422 367.00 pesos, being between 15 and 45% higher with respect to the individual production of each crop. For the selected crops, profits of 6 254 668.49 and 6 339 146.18 pesos were calculated for tomatoes and bell peppers, respectively.